2015
DOI: 10.1007/s10551-015-2826-7
|View full text |Cite
|
Sign up to set email alerts
|

Machiavellianism, Moral Orientation, Social Desirability Response Bias, and Anti-intellectualism: A Profile of Canadian Accountants

Abstract: Prior research has demonstrated that accountants differ from the general population on many personality traits. Understanding accountants' personality traits is important when these characteristics may impact professional behavior or ability to work with members of the business community. Our study investigates the relationship between Machiavellianism, ethical orientation (idealism, relativism), anti-intellectualism, and social desirability response bias in Canadian accountants. We find that Canadian accounta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 64 publications
0
10
0
1
Order By: Relevance
“…This study will contribute to the development of the literature, given the small number of studies in this area in Portugal. On the other hand, although several studies have investigated how some accountants' personality traits interact with other variables (Triki et al, 2017), we have not identified studies at the international level that assess the effect of the individual characteristics of certified accountants on the need to mitigate AEMP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study will contribute to the development of the literature, given the small number of studies in this area in Portugal. On the other hand, although several studies have investigated how some accountants' personality traits interact with other variables (Triki et al, 2017), we have not identified studies at the international level that assess the effect of the individual characteristics of certified accountants on the need to mitigate AEMP.…”
Section: Discussionmentioning
confidence: 99%
“…People are different from each other, however, some behaviors are identical in different people. People According to Triki et al (2017), understanding the individual traits of accountants is important when these characteristics can influence professional behavior or the ability to work with members of the business community. Nogueira and Fari (2007) found that personality traits (related to the way of being, thinking, acting, among others) influence the choices/perceptions of professionals in any area of activity.…”
Section: Rq6 What Corporate Governance Mechanisms Can Mitigate Aemp?mentioning
confidence: 99%
“…Menurut Triki, Cook, & Bay (2015) individu dengan tingkat Mach rendah dianggap lebih jujur dan peduli, mereka juga lebih terbuka terhadap masalah orang lain. Sehingga akan lebih mungkin melakukan tindakan whistleblowing.…”
Section: Pendahuluanunclassified
“…As alluded to previously, researchers regularly develop hypotheses that suggest dubious ethics among high relativists motivated by self‐interest. These are often based on assumptions, for example, that “relativism is associated with less ethical decision making” (Triki, Cook, & Bay, , p. 625) and low self‐control (Arli & Leo, , Hypothesis 2), that “egocentricity” (Huang & Tsai, , p. 803), and “solipsism” (Aguirre et al, , p. 123) characterize relativistic individuals, that adherents to relativistic approaches “easily ignore socially expected conduct” such as helping others (Chuang & Chiu, , p. 52), “espouse a moral philosophy based on personal whims or the expediency of the moment” (Kung & Huang, , p. 484), and “have no strong constraints against engaging in deviance” (Hastings & Finegan, , p. 692).…”
Section: Assumptions Of Questionable Ethics In Relativismmentioning
confidence: 99%